Quantification of the antimalarial piperaquine in plasma. - Tarning, J; Lindegardh, N (2008)
Malaria is one of the most common parasitic diseases in the world, with up to three million deaths a year. Piperaquine is an antimalarial drug that was extensively used in China during the 1980s and has recently received renewed interest as a partner drug in artemisinin-based combination therapy. Despite extensive use, the first bioanalytical method was published in 2003. In total there are eight previously published methods for quantification of piperaquine in different biological matrices using HPLC with UV or tandem mass spectrometric detection. Five of these allow for quantification of piperaquine in plasma and are discussed in this paper.